Evaluation of Nootropic Potential of Green Peas in Mice - Sushila Kaura, Milind Parle (Journal of Applied Pharmaceutical Science, 2017)
Green Peas are tiny powerhouse of nourishment. They are rich in alpha-linolenic acid, flavonoids, carotenoids, phenolic acids, polphenols and pisumsaponins. The present study was employed to assess nootropic potential of Green Peas (Pisum sativum). Elevated Plus Maze model and Passive avoidance Paradigm served as Exteroceptive Behavioral models. Scopolamine and ethanol were used as amnesic agents. Pisum sativum (PS) in two different concentrations (2.5% w/w and 5% w/w) were administered with diet, for 15 successive days to mice. A decrease in transfer latency and increase in step down latency was observed. Further, green peas ameliorated memory deficits induced by scopolamine and ethanol in mice. PS produced significant increase in brain Glutathione levels, declined brain Malondialdehyde levels and reduced brain Acetylcholinesterase activity. Therefore, behavioral effects of PS would be worthwhile in management of cognitive dysfunctions.
Keywords: Pisum sativum, Memory, Alpha linolenic acid, Pisumsaponins, Neurodegeneration, Cognitive deficits.